Mastoid pneumocoele with skull base and cervical spine pneumatisation. Issue 5 (9th May 2013) - Cowan, Ian A; Greig, Sam R; Bird, Philip A
Summary Very uncommonly, Eustachian tube dysfunction can lead to symptomatic chronic elevation of middle ear pressure with aeration of bone and adjacent structures in the skull base and upper cervical spine, and an increased risk of fracture. We present a case demonstrating the natural history of this condition over 11 years before treatment and 10 months after treatment.